Wykorzystanie koncepcji klastra jako narzędzia poprawy konkurencyjności przedsiębiorstw lokalnych - Rosińska, Magdalena (Cluster Concept as a Tool of the Local Enterprises' Competitiveness Improvement, 2007)
The aim of the paper is presentation of the network attitude as one of possible models of the local enterprises' competitiveness improvement. The concept of the cluster is described. It is understood as a kind of network which results in spatial concentration of the subjects specialized in the given area and gaining specific advantages. The author points two basic presumptions of cluster-type connection in the area - time and positive local circumstances. The strengthening of the partners' attachments is a process, developing in time and divided into periods. The additional requirement of enterprise success is positive attitude towards such models development which is exemplified in local development policy. The cluster, as a regional hub, is a basis for creation of competitiveness advantage of the global character because specific regional factors are value added to standard.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 411-418